Early vitrectomy to reverse macular dragging in a one-month-old boy with familial exudative vitreoretinopathy - Iwata, Akiko (Am J Ophthalmol Case Rep, 2019)
PURPOSE: Vitrectomy is usually only indicated for familial exudative vitreoretinopathy (FEVR) cases with progressive retinal folds or macular dragging. In this report, we present our experience reversing the progression of macular dragging by performing early eye vitrectomies in a 1-month-old male baby with FEVR. OBSERVATIONS: A 7-day-old, full-term male baby was examined by a pediatric ophthalmologist. His sister had a laser ablation treatment after being diagnosed with FEVR. The ophthalmologist found the baby had avascular retinas, fibrovascular membranes, and vitreous hemorrhages in both eyes, and performed retinal photocoagulations the next day. Although the retinal folds had not yet formed, the arcade vessels began to linearize after the procedure, strongly suggesting disease progression. Therefore, we performed lens-sparing vitrectomies in both eyes on the twenty-ninth day of life. After surgery, the macular dragging reversed, as evidenced by vascular arcade angle measurements. Three years after the surgery, the boy's visual acuity was 0.4 in both eyes. CONCLUSIONS AND IMPORTANCE: In this case, we believe the good postoperative outcomes were due to early vitrectomies before the vitreoretinal traction became severe. In addition, the retinal photocoagulation performed on the eighth day of life may have reduced disease activity, at least partially. This case highlights the importance of prompt diagnosis and appropriate treatment of FEVR.